Patients With Symptomatic AAAs Are More Likely to Develop Lumen Partial-Thrombus After Endovascular Aortic Repair Than Asymptomatic Patients - Wang, Enci; Xie, Xinsheng; Xu, Dandan; Shu, Xiaolong; Zhao, Yu fei; Zhang, Yuchong; Lin, Peng; Guo, Daqiao; Fu, Weiguo; Wang, Lixin (Frontiers in Cardiovascular Medicine, 2022)
Background: According to their symptoms, abdominal aortic aneurysms (AAAs) can be divided into symptomatic and asymptomatic types. This study aimed to explore the differences and correlations between postoperative lumen thrombosis in these two groups after endovascular aortic repair (EVAR). Methods: A retrospective study using clinical data of 169 patients with AAA treated with EVAR collected in our hospital between January 2018 and January 2021 was conducted based on the inclusion and exclusion criteria for patient selection. Based on whether the patient had clinical symptoms at admission and the presence of a complete lumen thrombus during follow-up, the patients were divided into two sets of groups: a complete-thrombus group (n = 44) and a partial-thrombus group (n = 125), and a group with clinical symptoms (n = 32) and a group without clinical symptoms (n = 137). The clinical data of these groups were compared, and a further stratified analysis was performed. Results: A total of 169 patients were included in the analysis. An abdominal aorta stent graft was successfully implanted in all patients. The complete-thrombus rate of the patients in this study was 73.96%. Univariate analysis showed that the maximal aortic diameter and preoperative peripheral blood neutrophil levels affected the clinical symptoms of patients with AAA (p < 0.05). The complete thrombus rate of the lumen of the AAA was lower in patients with clinical symptoms than in those without symptoms during the follow-up period (p < 0.05). Female sex, preoperative hyperuricemia, and symptoms at admission were independent risk factors for a partial thrombus in the lumen during follow-up. Based on these independent risk factors, we constructed a scoring system to differentiate patients into low- (0 points), middle- (1 point), and high-risk (2 points) groups. The scoring system could distinguish the complete lumen thrombosis rate after EVAR to a certain extent. Conclusions: Patients with symptomatic AAAs were more likely to develop incomplete lumen thrombosis than asymptomatic patients during follow-up after EVAR.